Penggambaran Tokoh dan Fungsi Pelaku dalam Cerita Rakyat Momotaro (TEORI VLADIMIR PROPP) - Khotimah, Khusnul (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
Folk tales are part of fictional literary works which fall into the category of oral folklore. In Japan, folklore is called minwa and is categorized into 3 groups, namely Shinwa, Densetsu, and Mukashibanashi. Mukashibanashi or fairy tales are oral literary works that are spread by word of mouth. Momotaro is a famous fairy tale originating from Japan. The momotaro story describes the figure of a child born from a fruit, namely the momo (peach). This research will focus on the depiction of characters/actors and the function of the actor in the Momotaro story using Vladimir Propp's actor function theory. This research uses a structuralism approach. This type of research is qualitative with descriptive analysis methods. The aim of this research is to describe the depiction of the characters and the function of the actors from the Momotaro folklore. From the research results, 12 data were found. With each data classified based on 7 character depictions in the style of Vladimir prop. However, of the 7 character depictions, only 4 were found, namely villains, donors, helpers and heroes. Then, of the 31 functions of Vladimir Propp, only 9 were found, namely the villainy function, Absentation function, Provision or receipt of a magical agent function, mediation function of the connective incident, beginning counteraction function, spatial translocation function, struggle function, victory function and return function.